Associations between the oxidative balance score and constipation: a cross-sectional study of the NHANES, 2005-2010 - Yuchao Wang; Jiao Li; Wei Sun; Yunbin Tong; Lu Han; Ziying Jiang; Weili Xu; Daqing Sun (BMC, 2024)
Abstracts Objective The oxidative balance score (OBS) reflects the overall burden of oxidative stress in an individual, with a higher OBS indicating greater antioxidant exposure. This study aimed to explore the association between constipation and OBS. Methods Variables were extracted from participants who completed a constipation questionnaire as part of the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2010. The OBS was developed based on dietary and lifestyle factors, encompassing 16 nutrients and 4 lifestyle variables. Weighted logistic regression and restricted cubic spline (RCS) analyses were employed to evaluate the association between OBS and constipation. Results After adjusting for all covariates, weighted multivariate logistic regression analysis revealed a 4% reduction in the incidence of constipation for each additional unit of OBS (OR: 0.96, 95% CI: 0.95-0.97, p < 0.001). In the OBS subgroup, the risk of constipation significantly decreased compared to that in the lowest quartile (Q2: 0.72, P = 0.024; Q3: 0.59, P < 0.001; Q4: 0.54, P < 0.001). Conclusions The present study demonstrated a significant association between constipation and the oxidative balance score (OBS), particularly dietary OBS, and that an increase in OBS may reduce the risk of developing constipation, in which oxidative stress may play an important role. This finding suggested that dietary modification could be an important approach for preventing constipation.